On-line estimation of alternators rotor angle dynamics in the modern power system. (January 2022) - Kumar, Mukesh; Affijulla, Shaik
Highlights: Development of a simple, robust and computationally efficient alternator rotor angle estimation methodology. Introduction of empirical synchronous reactance to extract the alternator rotor dynamics. Proposed a new methodology to monitor the alternator rotor dynamics in the grid. Suitable on-line monitoring solution for visualization of alternators rotor dynamics in the smart power networks. Abstract: On-line monitoring of synchronous rotor angle stability is a challenging task in the large interconnected complex power system. Now-a-days, Phasor Measurement Units (PMUs) are incorporated for wide area visualization of various electric grid parameters. In this paper, interconnected alternators rotor angle estimation methodology based on empirical modelled time varying synchronous reactance and PMU voltage/current phasors is proposed. Further, an empirical synchronous reactance is modelled to characterize the alternator rotor dynamics under various abnormal scenarios. The efficacy of proposed rotor dynamics estimation approach has been validated on WSCC 9- bus and Siemens 23-bus test power systems under different fault conditions by varying fault impedance. The simulation result reveal that the proposed estimation methodology has effectively captured the alternator rotor dynamics during peculiar abnormal environments. Thus, the proposed work can be best suitable for on-line monitoring of alternators rotor angle dynamics to enhance the reliability and security operations in the modern smart electric grids.